2019
DOI: 10.1002/eqe.3215
|View full text |Cite
|
Sign up to set email alerts
|

Test and analysis of reinforced concrete (RC) precast shear wall assembled using steel shear key (SSK)

Abstract: Summary Reinforced concrete (RC) precast shear walls are extensively applied in practical engineering, owing to their fast construction speed. However, because of the transport conditions, RC precast shear walls have to be separated into small wall segments during the factory prefabrication procedure before being assembled on site. Typically, wet‐type jointing methods are adopted to link the segments, which is time‐consuming and results in unreliable post‐pouring area strength. To overcome this problem, the no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…23 It can be observed from the hysteretic loops that the shear walls exhibited similar deformation ability and hysteretic properties because they are of the same CR. 7 The differences of initial stiffness and energy dissipation are listed in Figure 19. As y d decreased from 0.1 to 0.01 mm, the initial stiffness of the HSK shear wall increased by 14%, the energy dissipation increases by 8%.…”
Section: Parametric Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…23 It can be observed from the hysteretic loops that the shear walls exhibited similar deformation ability and hysteretic properties because they are of the same CR. 7 The differences of initial stiffness and energy dissipation are listed in Figure 19. As y d decreased from 0.1 to 0.01 mm, the initial stiffness of the HSK shear wall increased by 14%, the energy dissipation increases by 8%.…”
Section: Parametric Analysismentioning
confidence: 99%
“…Over the decades, numerous studies have been carried out to develop a variety of joints for prefabricated structures, including joints with grouted sleeve splices, 1,2 joints with unbonded posttensioned tendons (UPTs), [3][4][5][6] and joints with welded construction. 7,8 On this basis, Smith et al 9 and Shen et al 10 proposed two new prefabricated structural systems that allow free arrangement of shear walls, making the design and construction more flexible.…”
Section: Introductionmentioning
confidence: 99%
“…Sun et al [20,21] experimentally studied the cyclic behavior of precast shear wall with bolt-steel connections. Shen et al [22] carried out cyclic load tests of a new type of PC wall connected by steel shear key, and the test result indicated that the proposed wall specimen exhibits satisfactory bearing capacity and deformability.…”
Section: Rebars Of Upper Pc Elementmentioning
confidence: 99%
“…The prefabricated wall segments can be directly transported from factories and assembled on the construction site. Diverse approaches for wall segments assembling have been proposed and studied in the recent decade, including but not limited to dry connectors, [5][6][7][8][9][10] unbonded posttensioned (UPT) strands, [11][12][13] grout-filled sleeves, 14,15 etc. Among them, dry connectors with welding or bolting configurations completely eliminate the process of concrete casting during assembly.…”
mentioning
confidence: 99%
“…Among them, dry connectors with welding or bolting configurations completely eliminate the process of concrete casting during assembly. Specifically, Shen et al 5,6 developed an innovative shear key which is welded onto the embedded steel panels of adjacent wall segments for load transfer. The shear keys exhibited satisfactory fatigue properties and energy dissipation capacity because of their optimized boundary shapes 7 ; Belleri et al 8,9 proposed a precast wall segment with reserved rectangular slots, where the main reinforcement of adjacent wall segments is fastened by high strength bolts and hooks.…”
mentioning
confidence: 99%